What Level of Migration Is Required to Achieve Zero Population Growth in the Shortest Possible Time? Asian Examples - McDonald, Peter; Hosseini-Chavoshi, Meimanat (Frontiers in Human Dynamics, 2022)
Sustained below replacement fertility leads to declining population size. Several countries in Asia have experienced below replacement fertility for many years. The paper applies a novel approach to examining the viability of using immigration to achieve zero population growth in six Asian countries: China, Japan, Republic of Korea, Thailand, Singapore and Australia. The novel approach is to estimate the level of immigration that would be required to maintain a constant annual number of births in the long term. Maintaining the number of births at the current level is the fastest way to achieve eventual zero population growth. A population with a constant annual number of births, labelled as a quasi-stationary population, also has a near-to constant age structure that is not excessively old. The study concludes that, for all countries except Australia, no reasonable level of immigration could produce a quasi-stationary population if fertility remains at the country’s 2020 level. The constraining factors are the current population size and level of fertility and the extent to which there is acceptance of permanent immigrants in the country. If fertility were to increase over 15-20 years to 1.7 births per woman and the country was accepting of relatively large numbers of permanent immigrants, the quasi-stable outcome becomes potentially viable for all countries except China